A Single‐Stage Differential Amplifier Using Organic Electrochemical Transistors - Farnaz Fahimi Hanzaee; Ivan B. Dimov; Luke W. Gatecliff; Richard H. Bayford; George G. Malliaras; Andreas Demosthenous; Nick de N. Donaldson (Advanced Electronic Materials)
Abstract Organic electrochemical transistors (OECTs) are attractive devices, particularly for biomedical applications. The inherent quality of OECTs in amplifying signals, combined with the possibility of directly interfacing with biological tissue, make them unique candidates to replace recording electrodes with the added advantage of providing on‐site amplification (and thus allowing them to be counted as active electrodes). While most amplifiers using OECTs are transconductance amplifiers, having voltage‐to‐voltage amplification is more desirable in many applications to make the output compatible with any downstream conditioning circuit. Differential recording of physiological signals has the benefit of rejecting the common‐mode noise sourcing from the environment or the body itself while amplifying the desired signal. Here the considerations for and challenges of designing an OECT‐based differential amplifier are discussed and a three‐transistor amplifier is proposed that can provide a common‐mode rejection ratio of up to ≈20 dB. To demonstrate its advantage, a differential amplifier is used to record ECG signals from a human volunteer, and the collected data is compared with recordings from a Wheatstone bridge OECT amplifier, showing the improved signal‐to‐noise ratio, gain, and power consumption.